Optimization of Perioperative Conditions to Prevent Ischemic Cholangiopathy in Donation After Circulatory Death Donor Liver Transplantation. Issue 8 (August 2016) - Kubal, Chandrashekhar; Mangus, Richard; Fridell, Jonathan; Saxena, Romil; Rush, Natalia; Wingler, Matthew; Ekser, Burcin; Tector, Joseph
Abstract : Background: Donation after circulatory death (DCD) donor pool remains underutilized for liver transplantation (LT). We describe optimizing "modifiable risk factors, " such as cold ischemia time (CIT) recipient warm ischemia time (WIT) and the use of thrombolytic flush at the time of procurement to minimize ischemic cholangiopathy (IC). Methods: From July 2011 (era II), to improve outcomes after DCD LT, measures were taken to minimize CIT, operative time and recipient WIT along with the use of tissue plasminogen activator (tPA) flush during DCD procurements. Thirty consecutive DCD LTs were performed prospectively in era II. Outcomes were compared with 61 historic controls (era I). Reperfusion biopsies were evaluated for the presence of necrosis and biliary epithelial damage. Results: Median CIT (4.9 [3.5-5.9] vs 6.4 [4.3-12]; P < 0.001), hepatectomy time (70 [42-120] vs 81 [58-207]; P = 0.02), and recipient WIT (16 [13-31] vs 24[15-40]; P < 0.001) were significantly shorter in era II. All patients in era II received tPA flushed liver grafts. None of the patients in era II developed IC (0% vs 18%; P = 0.013). There were fewer biliary complications in era II, and there was no increased risk of bleeding associated with the use of tPA. One-year graft survival was slightly better in era II (n = 24 patients with 1 year follow-up) (88% vs 80%; P = 0.14). Conclusions: Optimizing peritransplant conditions, such as shortening ischemic times with the use of thrombolytic donor flush, may prevent IC after DCD LT. With this approach, the DCD donor pool may be expanded. Abstract : Improved selection timing and the use of tissue plasminogen activator flush was associated with a decrease in biliary complications in a single center study of DCD outcomes.